A soft magnetic core and its preparation method and application

By smelting alloys, phosphating treatment and resin coating under an inert atmosphere, and preparing soft magnetic cores combined with cold pressing and heat treatment technologies, the problem of difficult to balance magnetic permeability and magnetic loss in the existing process is solved, and the preparation of high-performance soft magnetic cores is achieved.

CN119495507BActive Publication Date: 2025-04-22HANGZHOU XINCHUAN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510070326.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

In the existing soft magnetic core preparation process, it is difficult to balance each process link, resulting in insufficient magnetic permeability and magnetic loss, making it difficult to develop high-performance soft magnetic cores.

Method used

Various raw materials are mixed and heated to melt into an alloy under an inert atmosphere, forming mixed steam and condensing to collect the alloy powder, and the soft magnetic core is prepared by phosphating treatment and resin coating, combined with cold pressing and heat treatment technology.

Benefits of technology

The soft magnetic core prepared by this method has a high density and hardness, and the core loss is reduced and the performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495507B_ABST
    Figure CN119495507B_ABST
Patent Text Reader

Abstract

The present invention discloses a soft magnetic core and a preparation method and application thereof, and relates to the technical field of magnetic materials. The specific preparation method comprises: first, in an inert atmosphere, various raw materials are mixed, heated and melted into an alloy, and then the mixed steam is condensed and collected to obtain alloy powder; then the alloy powder is added to a phosphating solution, and dried to obtain a phosphating alloy powder; then a resin and an auxiliary agent are added to a solvent, and then the phosphating alloy powder is added and mixed, and finally dried to obtain a soft magnetic alloy powder; a release agent is added to the soft magnetic alloy powder, and then a sample is obtained by cold pressing, and the sample is subjected to heat treatment to obtain a soft magnetic core. The soft magnetic core prepared by the present invention has a higher density and hardness, and has a lower core loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to a soft magnetic core and a preparation method and application thereof. Background Art

[0002] Soft magnetic materials are magnetic materials with low coercivity and high magnetic permeability. They are easy to magnetize and demagnetize, and are reflected in the hysteresis loop as being more slender. Their main functions are the conversion and transmission of magnetic conductivity and electromagnetic energy. They are widely used in various electrical circuits. Especially with the EV / green energy transformation, the demand for power transmission and control of electrical circuits has increased significantly, catalyzing the rapid iteration of soft magnetic material demand and technical processes. The soft magnetic core preparation process mainly includes four steps: powder making, insulation coating, pressing, and heat treatment. Although the soft magnetic powder preparation process is short, each process is closely linked. Powder making is the core link of magnetic powder core production. The formula and particle size play a decisive role in the product density and magnetic permeability. Water atomization and gas atomization are the mainstream processes. The selection of insulation coating process and materials mainly affects the loss performance of magnetic powder core and is the key to reducing eddy current loss. During the pressing process, as the pressing pressure increases, the magnetic permeability of the material will increase and the iron loss will decrease. However, when the pressure value exceeds a certain value, the magnetic loss will increase instead. This is because the coating layer is damaged due to excessive pressure. Heat treatment is to release the residual stress inside the material after pressing and improve the mechanical properties, but the heat treatment temperature is limited by the heat resistance of the insulation coating material. Therefore, it is of great significance to balance each process and develop and prepare high-performance soft magnetic cores. Summary of the invention

[0003] The purpose of the present invention is to provide a soft magnetic core and a preparation method and application thereof, so as to meet the development needs of the soft magnetic core preparation process, improve the soft magnetic core preparation process, and obtain a soft magnetic core with high performance.

[0004] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:

[0005] The invention discloses a method for preparing a soft magnetic core, comprising:

[0006] S1: In an inert atmosphere, various raw materials are mixed, heated and melted into an alloy, and further heated to form a mixed vapor, and the mixed vapor is condensed and collected to obtain alloy powder;

[0007] S2: adding alloy powder into phosphating solution and drying to obtain phosphating alloy powder; then adding resin and additive into solvent, adding phosphating alloy powder and mixing, and finally drying to obtain soft magnetic alloy powder; the resin is borosilicate resin and epoxy resin; borosilicate resin and epoxy resin are used together for coating, which has excellent stability and insulation, can effectively improve the density and hardness of soft magnetic core, that is, improve the mechanical properties of soft magnetic core, and at the same time, can effectively isolate eddy current, thereby reducing core loss;

[0008] S3: adding a release agent to the soft magnetic alloy powder and mixing, then cold pressing to obtain a sample, and heat treating the sample to obtain a soft magnetic core.

[0009] Preferably, the raw materials in S1 are iron, nickel, manganese, chromium, aluminum and silicon.

[0010] More preferably, the mass ratio of iron to nickel is 1:1-2; the mass ratio of iron to manganese is 1:0.001-0.02; the mass ratio of iron to chromium is 1:0.001-0.02; the mass ratio of iron to aluminum is 1:0.001-0.02; the mass ratio of iron to silicon is 1:0.001-0.02.

[0011] Preferably, the phosphating solution in S2 is a phosphoric acid solution, the phosphoric acid solution consists of phosphoric acid and acetone, the usage ratio of phosphoric acid to acetone is 1g:80-120ml, and the usage ratio of alloy powder to phosphoric acid solution is 1g:0.8-2ml.

[0012] Preferably, the solvent in S2 is acetone.

[0013] Preferably, in S2, the mass ratio of borosilicate resin to epoxy resin is 1:0.1-1, the mass ratio of borosilicate resin to solvent is 1g:8-20ml, and the mass ratio of phosphide alloy powder to epoxy resin is 1:0.01-0.025.

[0014] Preferably, the auxiliary agents in S2 are γ-aminopropyltriethoxysilane and diaminodiphenyl sulfone, the mass ratio of epoxy resin to γ-aminopropyltriethoxysilane is 1:0.1-0.2, and the mass ratio of epoxy resin to diaminodiphenyl sulfone is 1:0.1-0.2.

[0015] Preferably, the release agent in S3 is barium stearate, and the mass ratio of the soft magnetic alloy powder to the release agent is 1:0.002-0.005.

[0016] Preferably, the drying temperature in S2 is 55-100°C.

[0017] The invention also discloses an inductor, comprising the soft magnetic core prepared by the method.

[0018] The invention discloses a method for preparing a soft magnetic core, comprising:

[0019] S1: In an inert atmosphere, various raw materials are mixed, heated and melted into an alloy, and further heated to form a mixed vapor, and the mixed vapor is condensed and collected to obtain alloy powder;

[0020] S2: adding the alloy powder to the phosphating solution and drying at 55-100°C to obtain the phosphating alloy powder; then adding the resin and the additive to the solvent, adding the phosphating alloy powder and mixing, and finally drying at 55-100°C to obtain the soft magnetic alloy powder;

[0021] S3: Add a release agent to the soft magnetic alloy powder and mix, then cold press at 700-1000 MPa for 8-15 seconds to obtain a sample, keep the sample at 75-85°C, 115-125°C and 155-165°C for 3-8 minutes, and finally keep it at 175-185°C for 0.5-2 hours to obtain a soft magnetic core.

[0022] Preferably, the raw materials in S1 are iron, nickel, manganese, chromium, aluminum and silicon.

[0023] More preferably, the mass ratio of iron to nickel is 1:1-2.

[0024] More preferably, the mass ratio of iron to manganese is 1:0.001-0.02.

[0025] More preferably, the mass ratio of iron to chromium is 1:0.001-0.02.

[0026] More preferably, the mass ratio of iron to aluminum is 1:0.001-0.02.

[0027] More preferably, the mass ratio of iron to silicon is 1:0.001-0.02.

[0028] Preferably, the phosphating liquid in S2 is a phosphoric acid solution, the phosphoric acid solution consists of phosphoric acid and acetone, and the usage ratio of phosphoric acid to acetone is 1g:80-120ml.

[0029] Preferably, the usage ratio of alloy powder to phosphating solution in S2 is 1g:0.8-2ml.

[0030] Preferably, the solvent in S2 is acetone.

[0031] Preferably, the mass ratio of the borosilicate resin to the epoxy resin in S2 is 1:0.1-1.

[0032] Preferably, the usage ratio of borosilicate resin to solvent in S2 is 1 g: 8-20 ml.

[0033] Preferably, the mass ratio of the phosphating alloy powder to the epoxy resin in S2 is 1:0.01-0.025.

[0034] Preferably, the auxiliary agent in S2 is γ-aminopropyltriethoxysilane and diaminodiphenyl sulfone.

[0035] More preferably, the mass ratio of the epoxy resin to γ-aminopropyltriethoxysilane is 1:0.1-0.2, and the mass ratio of the epoxy resin to diaminodiphenyl sulfone is 1:0.1-0.2.

[0036] Preferably, the release agent in S3 is barium stearate, and the mass ratio of the soft magnetic alloy powder to the release agent is 1:0.002-0.005.

[0037] The present invention discloses a method for preparing borosilicate resin, which is specifically:

[0038] 3-glycidyloxypropylmethyldiethoxysilane, (3-nitrileisobutyl)triethoxysilane and boric acid were added to anhydrous ethanol, the temperature was raised to 65-75°C, and hydrochloric acid solution and water were added, and the reaction was continued for 3-5 hours. After the reaction was completed, the borosilicate resin was obtained by vacuum distillation.

[0039] Preferably, the molar ratio of 3-glycidyloxypropylmethyldiethoxysilane to (3-nitrileisobutyl)triethoxysilane is 1:1-2.

[0040] Preferably, the molar ratio of boric acid to 3-glycidyloxypropylmethyldiethoxysilane is 1:1.5-2.5.

[0041] Preferably, the usage ratio of 3-glycidyloxypropylmethyldiethoxysilane to anhydrous ethanol is 1 mol: 2-5 L.

[0042] Preferably, the hydrochloric acid solution consists of hydrochloric acid and water, and the usage ratio of hydrochloric acid to water is 1 mol: 0.8-1.2L.

[0043] Preferably, the usage ratio of 3-glycidyloxypropylmethyldiethoxysilane to the hydrochloric acid solution is 1 mol: 0.5-1 ml.

[0044] Preferably, the ratio of boric acid to water is 1 mol: 0.8-2L.

[0045] Preferably, after the reaction is completed, the temperature of the reduced pressure distillation is 120-150° C. and the time is 1-3 h.

[0046] The present invention discloses a method for preparing an epoxy resin, which specifically comprises:

[0047] S-(4-hydroxyphenyl) 4-hydroxybenzenesulfonylthioate, epichlorohydrin and benzyltriethylammonium chloride were mixed, heated to 120-130°C under nitrogen conditions and reacted for 1-2.5 hours. After the reaction was completed, the mixture was cooled to 50-60°C, and then sodium hydroxide solution was added, and the reaction was continued for 3-5 hours, and then cooled to 20-30°C. The supernatant was washed and rotary evaporated to obtain epoxy resin.

[0048] Preferably, the usage ratio of S-(4-hydroxyphenyl)4-hydroxybenzenesulfonylthioate to epichlorohydrin is 1 mmol:1.8-3 ml.

[0049] Preferably, the molar ratio of S-(4-hydroxyphenyl) 4-hydroxybenzenesulfonylthioate to benzyltriethylammonium chloride is 1:0.015-0.03.

[0050] Preferably, the sodium hydroxide solution consists of sodium hydroxide and water, and the dosage ratio of sodium hydroxide to water is 1 mol: 35-50 ml.

[0051] Preferably, the usage ratio of S-(4-hydroxyphenyl) 4-hydroxybenzenesulfonylthioate to sodium hydroxide solution is 1 mmol: 0.2-0.5 ml.

[0052] More preferably, in the preparation of the soft magnetic core, a coupling solution can be used on the basis of using borosilicate resin and epoxy resin. The use of the coupling solution can improve the bonding force and compatibility between the alloy powder and the coated resin, forming a uniform and continuous resin insulation coating layer, so that the prepared soft magnetic core has higher density and mechanical properties, and reduces the core loss.

[0053] Preferably, the mass ratio of the phosphide alloy powder to the coupling solution is 1:0.5-2.5.

[0054] The present invention discloses a coupling solution, which is specifically:

[0055] Add O-4-methylcoumarin-N-[3-(triethoxysilyl)propyl]carbamate to the ethanol aqueous solution, and react at 75-85° C. and pH 6-8 for 10-30 minutes to obtain a coupling solution.

[0056] The ethanol aqueous solution is composed of ethanol and water, the mass ratio of ethanol to water is 1:0.05, and the mass ratio of O-4-methylcoumarin-N-[3-(triethoxysilyl)propyl]carbamate to the ethanol aqueous solution is 1:150.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The present invention proposes a soft magnetic core and a preparation method and application thereof. First, various raw materials are mixed, heated and melted into an alloy under an inert atmosphere, and then heated to form a mixed steam. The mixed steam is condensed and collected to obtain alloy powder; then the alloy powder is added to a phosphating solution and dried to obtain a phosphating alloy powder; then a resin and an auxiliary agent are added to a solvent, and then the phosphating alloy powder is added and mixed, and finally dried to obtain a soft magnetic alloy powder; a release agent is added to the soft magnetic alloy powder and mixed, and then a sample is obtained by cold pressing, and the sample is heat treated to obtain a soft magnetic core. The soft magnetic core prepared by the present invention has a higher density and hardness, and has a lower core loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0060] Figure 1 This is the SEM image of the alloy powder. DETAILED DESCRIPTION

[0061] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0063] Embodiment 1:

[0064] Preparation of borosilicate resin: 3-glycidyloxypropylmethyldiethoxysilane, (3-nitrileisobutyl)triethoxysilane and boric acid were added to anhydrous ethanol, heated to 70°C, and then hydrochloric acid solution and water were added, and the reaction was continued for 4 hours. After the reaction was completed, the borosilicate resin was obtained by vacuum distillation at 130°C for 1.5 hours. The molar ratio of 3-glycidyloxypropylmethyldiethoxysilane to (3-nitrileisobutyl)triethoxysilane is 1:1.5, the molar ratio of boric acid to 3-glycidyloxypropylmethyldiethoxysilane is 1:2, the ratio of 3-glycidyloxypropylmethyldiethoxysilane to anhydrous ethanol is 1 mol:2.5L, the hydrochloric acid solution consists of hydrochloric acid and water, the ratio of hydrochloric acid to water is 1 mol:1L, the ratio of 3-glycidyloxypropylmethyldiethoxysilane to the hydrochloric acid solution is 1 mol:0.7ml, and the ratio of boric acid to the added water is 1 mol:1.03L.

[0065] Preparation of epoxy resin: S-(4-hydroxyphenyl) 4-hydroxybenzene sulfonyl thioester, epichlorohydrin and benzyl triethylammonium chloride are mixed, heated to 125°C and reacted for 1.5 hours under nitrogen. After the reaction is completed, the mixture is cooled to 55°C, and then sodium hydroxide solution is added, and the reaction is continued for 4 hours, and then cooled to 25°C, the supernatant is washed with water, and the epoxy resin is obtained by rotary evaporation. The molar ratio of S-(4-hydroxyphenyl) 4-hydroxybenzene sulfonyl thioester to epichlorohydrin is 1mmol:2.11ml, the molar ratio of S-(4-hydroxyphenyl) 4-hydroxybenzene sulfonyl thioester to benzyl triethylammonium chloride is 1:0.022, the sodium hydroxide solution is composed of sodium hydroxide and water, the molar ratio of sodium hydroxide to water is 1mol:40ml, and the molar ratio of S-(4-hydroxyphenyl) 4-hydroxybenzene sulfonyl thioester to sodium hydroxide solution is 1mmol:0.3ml.

[0066] Preparation of alloy powder: In an argon atmosphere, iron, nickel, manganese, chromium, aluminum and silicon are mixed, heated and melted into an alloy. Using the evaporation condensation method, the alloy is further heated to obtain a mixed vapor, which is condensed and collected to obtain an alloy powder. The mass ratio of iron to nickel is 1:1, the mass ratio of iron to manganese is 1:0.01, the mass ratio of iron to chromium is 1:0.01, the mass ratio of iron to aluminum is 1:0.01, and the mass ratio of iron to silicon is 1:0.01.

[0067] Preparation of soft magnetic alloy powder: The alloy powder is mixed with phosphoric acid solution, and then heated to 65°C and dried to obtain phosphating alloy powder. Then borosilicate resin, epoxy resin, γ-aminopropyl triethoxysilane and diaminodiphenyl sulfone are added to acetone, followed by adding phosphating alloy powder and mixing, and finally dried at 65°C to obtain soft magnetic alloy powder. The amount ratio of alloy powder to phosphoric acid solution is 1g:1ml, the phosphoric acid solution is composed of phosphoric acid and acetone, the amount ratio of phosphoric acid to acetone is 1g:100ml, the mass ratio of borosilicate resin to epoxy resin is 1:0.4, the mass ratio of borosilicate resin to acetone is 1g:10ml, the mass ratio of phosphating alloy powder to epoxy resin is 1:0.015, the mass ratio of epoxy resin to γ-aminopropyl triethoxysilane is 1:0.15, and the mass ratio of epoxy resin to diaminodiphenyl sulfone is 1:0.12.

[0068] Preparation of soft magnetic core: Add barium stearate to the soft magnetic alloy powder and mix, then cold press at 800MPa for 10s to obtain a ring sample with an outer diameter of 20mm, an inner diameter of 12mm, and a height of 6mm. Keep the ring sample at 80℃, 120℃, and 160℃ for 5min, and finally keep it at 180℃ for 1h to obtain the soft magnetic core. The mass ratio of soft magnetic alloy powder to barium stearate is 1:0.003.

[0069] Embodiment 2:

[0070] The preparation of borosilicate resin is the same as in Example 1.

[0071] The preparation of epoxy resin is the same as in Example 1.

[0072] The preparation of alloy powder is the same as in Example 1.

[0073] Preparation of soft magnetic alloy powder: The preparation of soft magnetic alloy powder in this embodiment is different from that in Example 1, except that the mass ratio of borosilicate resin to epoxy resin is 1:0.15, and other conditions and parameters are the same as in Example 1.

[0074] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 1, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0075] Embodiment 3:

[0076] The preparation of borosilicate resin is the same as in Example 1.

[0077] The preparation of epoxy resin is the same as in Example 1.

[0078] The preparation of alloy powder is the same as in Example 1.

[0079] Preparation of soft magnetic alloy powder: The preparation of soft magnetic alloy powder in this embodiment is different from that in Example 1, except that the mass ratio of borosilicate resin to epoxy resin is 1:0.8, and other conditions and parameters are the same as in Example 1.

[0080] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 1, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0081] Embodiment 4:

[0082] The preparation of borosilicate resin is the same as in Example 1.

[0083] The preparation of epoxy resin is the same as in Example 1.

[0084] Preparation of coupling solution: O-4-methylcoumarin-N-[3-(triethoxysilyl)propyl]carbamate was added to ethanol aqueous solution, and the reaction was carried out at 80°C and pH 7 for 15 minutes to obtain a coupling solution. The ethanol aqueous solution is composed of ethanol and water, the mass ratio of ethanol to water is 1:0.05, and the mass ratio of O-4-methylcoumarin-N-[3-(triethoxysilyl)propyl]carbamate to ethanol aqueous solution is 1:150.

[0085] The preparation of alloy powder is the same as in Example 1.

[0086] Preparation of soft magnetic alloy powder: The alloy powder is mixed with phosphoric acid solution, and then heated to 65°C and dried to obtain phosphated alloy powder. Then the phosphated alloy powder is added to the coupling solution and stirred for 1 hour to separate to obtain pretreated alloy powder. Borosilicate resin, epoxy resin, γ-aminopropyltriethoxysilane and diaminodiphenyl sulfone are added to acetone, and then the pretreated alloy powder is added and mixed, and finally dried at 65°C to obtain soft magnetic alloy powder. The usage ratio of alloy powder to phosphoric acid solution is 1g:1ml, the phosphoric acid solution is composed of phosphoric acid and acetone, the usage ratio of phosphoric acid to acetone is 1g:100ml, the mass ratio of phosphating alloy powder to coupling solution is 1:1.5, the mass ratio of borosilicate resin to epoxy resin is 1:1, the usage ratio of borosilicate resin to acetone is 1g:50ml, the mass ratio of phosphating alloy powder to epoxy resin is 1:0.015, the mass ratio of epoxy resin to γ-aminopropyltriethoxysilane is 1:0.15, and the mass ratio of diaminodiphenyl sulfone is 1:0.12.

[0087] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 1, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0088] Embodiment 5:

[0089] The preparation of borosilicate resin is the same as in Example 1.

[0090] The preparation of epoxy resin is the same as in Example 1.

[0091] The preparation of coupling solution is the same as Example 4.

[0092] The preparation of alloy powder is the same as in Example 1.

[0093] Preparation of soft magnetic alloy powder: The preparation of soft magnetic alloy powder in this embodiment is compared with that in Example 4, except that the mass ratio of the amount of phosphide alloy powder used to the coupling solution is 1:1.9, and other conditions and parameters are the same as in Example 4.

[0094] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 4, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 4.

[0095] Embodiment 6:

[0096] The preparation of borosilicate resin is the same as in Example 1.

[0097] The preparation of epoxy resin is the same as in Example 1.

[0098] The preparation of coupling solution is the same as Example 4.

[0099] The preparation of alloy powder is the same as in Example 1.

[0100] Preparation of soft magnetic alloy powder: The preparation of soft magnetic alloy powder in this embodiment is compared with that in Example 4, except that the mass ratio of the used amount of phosphating alloy powder and coupling solution is 1:1, and other conditions and parameters are the same as those in Example 4.

[0101] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 4, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 4.

[0102] Comparative Example 1:

[0103] The preparation of epoxy resin is the same as in Example 1.

[0104] The preparation of alloy powder is the same as in Example 1.

[0105] Preparation of soft magnetic alloy powder: The preparation of soft magnetic alloy powder in this embodiment is different from that in Example 1, except that borosilicate resin is not used, and other conditions and parameters are the same as in Example 1.

[0106] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 1, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0107] Comparative Example 2:

[0108] The preparation of borosilicate resin is the same as in Example 1.

[0109] The preparation of alloy powder is the same as in Example 1.

[0110] Preparation of soft magnetic alloy powder: The preparation of soft magnetic alloy powder in this embodiment is different from that in Example 1, except that epoxy resin is not used, and other conditions and parameters are the same as in Example 1.

[0111] Preparation of soft magnetic core: The preparation of the soft magnetic alloy powder in this embodiment is compared with that in Example 1, except that the soft magnetic alloy powder is the soft magnetic alloy powder prepared in this embodiment, and other conditions and parameters are the same as in Example 1.

[0112] Experimental Example 1:

[0113] The morphology of the alloy powder prepared in Example 1 was observed by SEM microstructure. Figure 1 As shown, the particle size of the alloy powder can be controlled within the range of 100-3000 nm.

[0114] Experimental Example 2:

[0115] The hardness of the soft magnetic cores prepared in Examples 1-6 and Comparative Examples 1-2 was measured. The soft magnetic cores were ground and polished before the test. The test force was 3000 kgf, the load holding time was 10 s, and 5 points were randomly selected on the surface of the magnetic ring for hardness testing, and the average value was finally taken.

[0116] Table 1 Hardness test results of soft magnetic core

[0117]

[0118] The results are shown in Table 1. Compared with Example 2, Example 1 of the present invention has a lower hardness of the soft magnetic core prepared in Example 2 than in Example 1, indicating that a reduction in the amount of epoxy resin used within a certain range will reduce the hardness of the soft magnetic core, that is, the mechanical property; Compared with Example 3, Example 1 shows that an increase in the amount of epoxy resin used within a certain range will increase the hardness of the soft magnetic core; Compared with Example 4, Example 1 shows that on the basis of using borosilicate resin and epoxy resin, pretreatment with a coupling solution can improve the hardness of the soft magnetic core; Compared with Example 5, Example 4 shows that an increase in the amount of coupling solution used within a certain range can improve the hardness of the soft magnetic core; Compared with Example 6, Example 4 shows that a reduction in the amount of coupling solution used within a certain range will reduce the hardness of the soft magnetic core; Compared with Comparative Examples 1 and 2, Example 1 shows that borosilicate resin and epoxy resin need to be used together, and any one of the borosilicate resin and epoxy resin alone will cause a decrease in the hardness of the soft magnetic core.

[0119] Experimental Example 3:

[0120] The core loss of the soft magnetic cores prepared in Examples 1-6 and Comparative Examples 1-2 was measured at 25°C, a frequency of 200kHz, and a maximum magnetic flux density of 0.05T.

[0121] Table 2 Core loss measurement results of soft magnetic core

[0122]

[0123] The results are shown in Table 2. Compared with Example 2, Example 1 of the present invention has a higher core loss of the soft magnetic core prepared in Example 2 than in Example 1, indicating that a reduction in the amount of epoxy resin used within a certain range will increase the core loss of the soft magnetic core; compared with Example 3, Example 1 shows that an increase in the amount of epoxy resin used within a certain range will reduce the core loss of the soft magnetic core; compared with Example 4, Example 1 shows that on the basis of using borosilicate resin and epoxy resin, pretreatment with a coupling solution can promote the coating and bonding of the alloy powder by borosilicate resin and epoxy resin, thereby reducing the core loss of the soft magnetic core; compared with Example 5, Example 4 shows that an increase in the amount of coupling solution used within a certain range can reduce the core loss of the soft magnetic core; compared with Example 6, Example 4 shows that a reduction in the amount of coupling solution used within a certain range will increase the core loss of the soft magnetic core; compared with Comparative Examples 1 and 2, Example 1 shows that borosilicate resin and epoxy resin need to be used together, and any one of borosilicate resin and epoxy resin alone will cause an increase in the core loss of the soft magnetic core.

[0124] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

[0125] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. A method for preparing a soft magnetic core, comprising: S1: In an inert atmosphere, various raw materials are mixed, heated and melted into an alloy, and further heated to form a mixed vapor, and the mixed vapor is condensed and collected to obtain an alloy powder; the raw materials are iron, nickel, manganese, chromium, aluminum and silicon; S2: adding alloy powder to phosphating solution, drying to obtain phosphating alloy powder; then adding resin and auxiliary agent to solvent, adding phosphating alloy powder to mix, and finally drying to obtain soft magnetic alloy powder; the resin is borosilicate resin and epoxy resin; the borosilicate resin is prepared from 3-glycidyloxypropylmethyldiethoxysilane, (3-nitrile isobutyl)triethoxysilane and boric acid; the epoxy resin is prepared from S-(4-hydroxyphenyl) 4-hydroxybenzenesulfonylthioate and epichlorohydrin; the mass ratio of borosilicate resin to epoxy resin is 1:0.1-1; the mass ratio of borosilicate resin to solvent is 1g:8-20ml, and the mass ratio of phosphating alloy powder to epoxy resin is 1:0.01-0.025; The auxiliary agents are γ-aminopropyltriethoxysilane and diaminodiphenyl sulfone, the mass ratio of epoxy resin to γ-aminopropyltriethoxysilane is 1:0.1-0.2, and the mass ratio of epoxy resin to diaminodiphenyl sulfone is 1:0.1-0.2; S3: adding a release agent to the soft magnetic alloy powder and mixing, then cold pressing to obtain a sample, and heat treating the sample to obtain a soft magnetic core.

2. The method for preparing a soft magnetic core according to claim 1, characterized in that: The mass ratio of iron to nickel in S1 is 1:1-2; the mass ratio of iron to manganese is 1:0.001-0.02; the mass ratio of iron to chromium is 1:0.001-0.02; the mass ratio of iron to aluminum is 1:0.001-0.02; and the mass ratio of iron to silicon is 1:0.001-0.

02.

3. The method for preparing a soft magnetic core according to claim 1, characterized in that: The phosphating solution in S2 is a phosphoric acid solution, which is composed of phosphoric acid and acetone, the usage ratio of phosphoric acid to acetone is 1g:80-120ml, and the usage ratio of alloy powder to phosphoric acid solution is 1g:0.8-2ml.

4. The method for preparing a soft magnetic core according to claim 1, characterized in that: The solvent in S2 is acetone.

5. The method for preparing a soft magnetic core according to claim 1, characterized in that: The mold release agent in S3 is barium stearate, and the mass ratio of the soft magnetic alloy powder to the mold release agent is 1:0.002-0.

005.

6. The method for preparing a soft magnetic core according to claim 1, characterized in that: The drying temperature in S2 is 55-100°C.

7. An inductor, comprising a soft magnetic core prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Low-loss high-entropy alloy soft magnetic powder core and preparation method thereof

    CN118737678A

  • Dust core and manufacture thereof

    JP1994029114A